2010
DOI: 10.5194/acp-10-3529-2010
|View full text |Cite
|
Sign up to set email alerts
|

A review of the theoretical basis for bulk mass flux convective parameterization

Abstract: Abstract. Most parameterizations for precipitating convection in use today are bulk schemes, in which an ensemble of cumulus elements with different properties is modelled as a single, representative entraining-detraining plume. We review the underpinning mathematical model for such parameterizations, in particular by comparing it with spectral models in which elements are not combined into the representative plume. The chief merit of a bulk model is that the representative plume can be described by an equatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 75 publications
0
40
0
Order By: Relevance
“…However, whether those clouds produce more precipitation relative to clouds with greater CDNC depends on moisture availability and evaporation (Stevens and Feingold, 2009), which are difficult for global models to predict (Plant, 2010). Observations have shown that convective clouds forming in regions of greater pollution, tend to have greater CDNC, which delays the onset of precipitation (Freud and Rosenfeld, 2012).…”
Section: Influence Of Entrained Aerosol Wet Scavenging On Cloud Propementioning
confidence: 99%
See 1 more Smart Citation
“…However, whether those clouds produce more precipitation relative to clouds with greater CDNC depends on moisture availability and evaporation (Stevens and Feingold, 2009), which are difficult for global models to predict (Plant, 2010). Observations have shown that convective clouds forming in regions of greater pollution, tend to have greater CDNC, which delays the onset of precipitation (Freud and Rosenfeld, 2012).…”
Section: Influence Of Entrained Aerosol Wet Scavenging On Cloud Propementioning
confidence: 99%
“…Particularly, for the case of convection, an ensemble of convective clouds at a variety of spatial scales is parameterized in each model grid box as a single entraining plume following the mass flux scheme of Tiedtke (1989). Further, the parameterization of convective precipitation (and hence wet scavenging) in global models is a notoriously challenging problem (Plant, 2010;Piriou et al, 2007;Randall et al, 2007;Arakawa, 2004). There is an ongoing need for better representation of convective cloud processes, and associated wet scavenging in global models, as our set of sensitivity simulations will indicate.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular method remains the use of a mass flux scheme (see e.g., Plant, 2010;Arakawa and Schubert, 1974). The latter aims to predict the vertical structure and evolution of a one-dimensional entraining-detraining plume (bulk mass flux scheme) or spectrum thereof (spectral mass flux scheme).…”
Section: Introductionmentioning
confidence: 99%
“…Bulk mass flux schemes such as Gregory and Rowntree (1990)and Kain (2004) consider a single, effective cloud rather than a spectrum of clouds carrying different mass fluxes (Plant, 2010). Such schemes therefore do not yield explicit results for m. In order to compare the convective fluctuations produced by different convection schemes, it is therefore more convenient to consider fluctuations in rainfall rather than mass flux.…”
Section: Rainfall Statisticsmentioning
confidence: 99%
“…By definition, the cloud-base mass flux to be computed as the closure of any mass-flux parametrization is a function of the large-scale forcing (Plant, 2010). Conventionally, the local, instantaneous grid-box state is used to approximate the large-scale environment.…”
Section: Implementation As a Stochastic Parametrizationmentioning
confidence: 99%